Agminate lichen aureus - Violeta Duarte Tortelly; Roberto Souto da Silva; Amanda Nascimento Cavalleiro de Macedo Mota; Juan Piñeiro-Maceira (Sociedade Brasileira de Dermatologia, 2013)
Lichen aureus is a rare variant of pigmented purpura, with a chronic and benign course. It is generally asymptomatic and often occurs in the lower limbs, presenting as erythematous brownish, coppery or golden macules and/or papules. The diagnosis is based on clinical and histopathological findings. The dermatoscopic pattern has been considered a useful tool in diagnosis presumption. We describe a case with a confluent morphological pattern, called agminate lichen aureus.